Myomectomy During Caesarean Section : A Safe Procedure - Akhter, Hasina; Khatun, Mst Rokeya (TAJ: Journal of Teachers Association, 2018)
Caesarean myomectomy which had traditionally been discouraged has recently frequently employed to remove myoma at the time of caesarean section. If myomectomy during caesarean delivery become a wide spread. Practice, it could potentially eliminate multiple surgeries for both indications. So, we decided to do caesarean myomectomy for dual indications. This was a prospective study was done in different private clinic in Rasjhahi from January 2012 to 2015. Total 20 pregnant women of different size fibroid were included in the study. Patients evaluated by age, Parity gestational age, any difficulty during operation, a blood loss during surgery and post operative complications. 20 cases were included in the study. There is no maternal mortality and as well as perinatal mortality. TAJ 2016; 29(1): 7-9